Terrorism and gender in Eye in the Sky and Zero Dark Thirty: women and girls on the war front in contemporary cinema - Ritzenhoff, Karen A. (Mediated terrorism in the 21st century, 2021)
In this chapter, Karen A. Ritzenhoff analyzes the question of modern warfare and “collateral damage”, especially when children are involved, in Eye in the Sky (2015) and Zero Dark Thirty (2012). These two war films both feature a prominent female lead making crucial decisions in the fight against international terrorism. Ritzenhoff argues that new technologies seamlessly used in this global war theatre add to the allure of the warzone action movie. In addition, she explains that these technologies render the hyper-masculinity of earlier war films redundant and that women can now assume a central role of masterminding counter terrorist attacks through the use of cyber-warfare.